ANALISIS WACANA KRITIS DI MEDIA SOSIAL (STUDI PADA FENOMENA PRO-KONTRA PENOLAKAN DAKWAH USTADZ ABDUL SOMAD) - Baiti Rahmawati; Abdul Muhid (Jurnal Dakwah Tabligh, 2019)
Da'wah and technological development are inseparable, this is based on the concept of contemporary da'wah that is easily accepted by the present, various new phenomena such as the case of rejection of clerics in several regions arise along with the rise of activity on social media, which incidentally is full of information which is not necessarily true (Tornberg & Tornberg, 2016: 132-134). The news of the pros and cons of rejecting the da'wah experienced by Ustadz Abdul Somad was forwarded freely on social media, one of the social media is twitter. In analyzing discourse on social media, especially Twitter, the author uses analysis technic of critical discourse analysis theory by Norman Fairclough to dismantle discourse practices (Eriyanto, 2015: 285), and includes Antonio Gramsci's theory of hegemony to see discourse battles (Ives, 2004: 63 ) in the phenomenon of Ustadz Abdul Somad's rejection. The results of this study include: (1) The issue of the affiliation of Ustadz Abdul Somad can be mediated with tabayyun and clarification through the media, both traditional and social. However, the issue of khilafah is growing until it displays a process of mutual accusation between the parties involved in the discourse of the khilafah revival; 2) The discourse of Ustadz Abdul Somad's rejection on social media in this study contains trends from two different ideologies namely Nahdlatul Ulama (NU), and Hisbut Tahrir Indonesia (HTI (3) The other tendencies are also influenced by political interests; 4) Between HTI and Banser has an impact on the image of Prabowo's and Jokowi's strongholds with the issue of the fight. HTI was identified as part of opposition supporters, while the impact on the Jokowi camp with anti-Islamic issues, because it was deemed not to show an attitude to clean up the chaos caused by burning the flag at the commemoration of the “Hari Santri Nasional.